Breast cancer patients with a pre-existing mental illness are less likely to receive guideline-recommended cancer treatment: A systematic review and meta-analysis - Katie Elliott; Emily Haworth; Iakov Bolnykh; R. Hamish McAllister-Williams; Alastair Greystoke; Adam Todd; Linda Sharp (Breast)
Breast cancer is the most commonly diagnosed cancer worldwide, with early detection and advanced treatments contributing to declining mortality rates. However, managing comorbid conditions, particularly mental illness, presents significant challenges for cancer treatment. This study systematically reviews and meta-analyses the impact of having a pre-existing mental illness on breast cancer treatment utilisation, focusing on specific treatments and comparing different mental illnesses. MEDLINE, EMBASE, CINAHL, and APA PsycInfo databases were searched. After screening, fifteen studies were identified as meeting the inclusion criteria. The included studies were predominantly from high-income countries, and compared breast cancer treatment in patients with and without pre-existing mental illnesses including anxiety, mood disorders, schizophrenia and psychotic disorders, and neurodevelopmental disorders. Meta-analysis revealed that patients with mental illnesses were significantly less likely to receive guideline-recommended treatments (OR = 0.78, 95 % CI 0.72–0.83, N = 5), chemotherapy (OR = 0.56, 95 % CI 0.34–0.78, N = 6), or radiotherapy (OR = 0.79, 95 % CI 0.66–0.93, N = 5). They were also significantly more likely to undergo mastectomy instead of breast-conserving surgery (OR = 1.38, 95 % CI 1.24–1.52, N = 4). Findings were consistent across different mental illnesses. This review highlights the need for targeted interventions to improve healthcare access and address provider biases, promoting better integration of mental health and oncology care.